Rapid technique of DNA-DNA in situ hybridisation on formalin fixed tissue sections using microwave irradiation. Issue 8 (August 1987) - Coates, P J; Hall, P A; Butler, M G; D'Ardenne, A J
Abstract : The relative sensitivities of different protocols for detecting cytomegalovirus nucleic acid sequences in histological specimens, using a biotinylated cDNA probe, were assessed. Several commonly used pre-treatment steps were not essential, nor was the use of a highly sensitive detection system. The choice of enzyme used for proteolytic digestion of tissue seems to be important, and increasing the temperature of denaturation of tissue and probe DNA to above 100 degrees C greatly increased the sensitivity of the method. Difficulties in achieving such high temperatures in a controlled manner were overcome by the use of a rapid microwave heating method that can be used routinely in laboratories. This technique detected cytomegalovirus infections in formalin fixed, paraffin processed tissue sections within a single working day.